Time is Bone: Streamlining the Diagnostic Pathway of Suspected Scaphoid Fractures with Cone-Beam CT - Maciejowski, Michał; Zdaniewicz, Mateusz; Baran, Adrian; Olejnik, Agnieszka; Adamiak, Jakub; Czyżak, Bartłomiej; Krukowski, Przemysław; Gąsior, Zuzanna; Gierlach, Agnieszka; Machowska, Anna (Quality in Sport, 2026)
Background: Scaphoid fractures present a significant diagnostic challenge in emergency departments. Conventional radiography frequently misses occult fractures, leading to either delayed diagnoses with severe complications or unnecessary, prolonged cast immobilization for healthy patients. While Magnetic Resonance Imaging (MRI) remains the gold standard, its high cost and limited availability restrict its routine use in acute settings. Cone-Beam Computed Tomography (CBCT) has emerged as a promising, accessible 3D imaging alternative. Objective: To evaluate the diagnostic accuracy of CBCT for suspected scaphoid fractures and assess its clinical utility regarding radiation dose and the optimization of the diagnostic pathway. Methods: A systematic review of PubMed, Europe PMC, and Cochrane databases was conducted up to March 2026. The review included original clinical studies providing quantitative data on the diagnostic performance of CBCT for scaphoid fractures in adult patients. Results: Six studies comprising 335 patients (106 with confirmed fractures) met the inclusion criteria. CBCT demonstrated high diagnostic validity, with sensitivity ranging from 88.9% to 100% and specificity between 96% and 100%. The median effective radiation dose (3.65–4.3 µSv) was significantly lower than that of standard multi-detector computed tomography (MDCT). Implementing early CBCT protocols reduced the median time to definitive diagnosis from 16.5 to 2.0 days, enabling 94.1% of patients to receive a conclusive diagnosis within 48 hours and reducing unnecessary fracture clinic attendances by 71.9%. Conclusions: CBCT provides diagnostic accuracy comparable to MRI with a highly favorable radiation safety profile. Integrating CBCT into routine clinical protocols for acute wrist trauma safely accelerates the diagnostic pathway, optimizes healthcare resources, and protects patients from unwarranted immobilization.